Smart Electronic Voting Machine Using IoT - G Rajesh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The basic concept of this mission is to create a digital voting sys- tem as a way to assist to get rid of defrauding of the manual voting structures like paper based voting system, in this there is a chance of casting vote more than once and prior. The proposed machine is which includes a couple of layers of verifications to ensure the reliability of the device. With the inclusion of biometric fingerprint sensor, every voter is entered into the gadget simplest after being diagnosed and checked with the given database of enlisted voters. Once the corresponding fingerprint is matched with the records provided, the voter will be allowed to proceed for selecting their preferred candidate from the panel of buttons. The final vote is then displayed onto a Liquid Cristal Display for the pride of voters. The proposed project displays transparency and also carries the characteristic of being autonomous for the duration of the path of operation.